ANALISIS FAKTOR YANG MEMENGARUHI RENDAHNYA PEMAKAIAN ALAT KONTRASEPSI IUD (INTRA UTERI DEVICE) OLEH IBU PASANGAN USIA SUBUR DI DESA SABUNGAN KECAMATAN SUNGAI KANAN KABUPATEN LABUHANBATU SELATAN TAHUN 2014 - albainah harahap; Heru Santosa; Maya Fitria (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Abstract To control the relatively high number of people the government is planning a national family planning program. IUD is a contraceptive option that is effective safe and comfortable for many women and high effectiveness in preventing pregnancy. In the village Sabungan contraceptive use is still low at only 0.08%. This research is dekskriptif by using factor analysis method eksplonatory application where the entire population of EFA mother who does not use contraceptives IUD in the Village River District Right Sabungan South Labuhanbatu district is 1290 EFA mother. While the sample used in this study are numbered 60 mothers EFA. From the research, there are 6 variables memngaruhi low use of contraceptive IUD (knowledge, attitudes, husband's support, the support of health, social, cultural, economic). After the due diligence factor in only 5 variables that can be analyzed further the knowledge, attitudes, husband support, support of health workers, the economy. And formed into 2 (two) external factors: the first factor yitu husband's support, the support of health professionals, and the second internal factor is the knowledge, attitudes, economics. It is therefore expected to provide FP correct and clear information about contraceptive IUD based on external and internal factors that can increase the IUD contraceptive users. Keywords: Contraception IUD, Spouses of Fertile Age, Factor Analysis